Communication Responsibilities of the International Agricultural Research Centers; Designing a Program Viewers Remember; Get the Facts, Not the Chicken: How to Use and Instructional Film; Precision Journalism; News Writing - Paul Gwin; Annette Sanders; Orrine Gregory; Joyce Lofstrom (Journal of Applied Communications, 1981)
Reviews of "Communication Responsibilities of the International Agricultural Research Centers," published by Agricultural Developmenl Council, Inc., and the International Rice Research Institute (IRRI); "Designing a Program Viewers Remember," by Gary A. Witt; and "Get the Facts, Not the Chicken: How to Use and Instructional Film," by Gary A. Witt; Precision Journalism, by Phillip Meyer; and News Writing<,em>, by George A. Hough III.